Pengembangan Buku Ajar Sastra Anak dalam Perspektif Multiple Intelligences untuk Penguatan Pendidikan Karakter Siswa Kelas 2 Sekolah Dasar - Nurul Dwi Oktaviana; Setya Yuwana Sudikan; Heru Subrata (LP. Ma'arif Janggan Magetan, 2023)
The study aims to develop learning products in the form of children's literature textbooks viewed from the perspective of multiple intelligences to strengthen character education for grade 2 elementary school students. The procedure in this study adapts the ADDIE development model which consists of five stages of development, namely Analysis, Design, Development, Implementation and Evaluation. Based on the results of the study, after carrying out the reliability test the next trial stage was the trial of the developed children's literature textbook product. The results of the research/findings show that the use of textbooks for elementary school students that have been developed is in accordance with the target audience, namely grade 2 elementary school students